Under Pressure: Interactions between Commensal Microbiota and the Teleost Immune System - Kelly, Cecelia; Salinas, Irene (Frontiers in Immunology, 2017)
Commensal microorganisms inhabit every mucosal surface of teleost fish. At these surfaces, microorganisms directly and indirectly shape the teleost immune system. This review provides a comprehensive overview of how the microbiota and microbiota-derived products influence both the mucosal and systemic immune system of fish. The cross talk between the microbiota and the teleost immune system shifts significantly under stress or disease scenarios rendering commensals into opportunists or pathogens. Lessons learnt from germ-free fish models as well as from oral administration of live probiotics to fish highlight the vast impact that microbiota have on immune development, antibody production, mucosal homeostasis and resistance to stress. Future studies should dissect the specific mechanisms by which different members of the fish microbiota and the metabolites they produce interact with pathogens, with other commensals and with the teleost immune system.